PERAN PROTEKTIF PEER SUPPORT TERHADAP STRES AKADEMIK MAHASISWA PAI DI LINGKUNGAN UIN PALANGKA RAYA - Ahmad Aspiani; Surawan Surawan (JOURNAL SAINS STUDENT RESEARCH, 2025)
Academic stress is a psychological condition commonly experienced by university students, including those in the Islamic Religious Education (PAI) Study Program at UIN Palangka Raya, due to academic demands such as assignments, exams, and performance expectations. One protective factor believed to help students cope with academic stress is peer support. This study aims to examine the relationship between peer support and academic stress levels among PAI students at UIN Palangka Raya. This research employed a quantitative method using questionnaires for data collection. The findings show that most students received a moderate level of peer support (50%), while 60% experienced a high level of academic stress. Pearson correlation analysis revealed a significant relationship between peer support and academic stress (Sig. < 0.05). These findings suggest that social support from peers plays a vital role in helping students manage academic stress, although it may not be sufficient to reduce stress levels entirely. Therefore, strengthening peer support should be integrated with other supportive strategies such as campus counseling services and stress management training to foster a healthy and supportive academic environment.